Analysis of The Use of Sawdust Waste As Concrete Mixture Add Material Against Workability and Compressive Strength Concrete With Three Concrete Treatment Methods - Syafwandi, Syafwandi; Setyo Sembodo, Danu; Tua Munthe, Agyanata; Sumarno, Agung (International Journal of Engineering, Science and Information Technology, 2021)
Wood management activities that are often encountered, as in wood cutting activities in the manufacture of wooden handicrafts, basically after this activity can become a problem, namely sawdust waste, where this waste if left for so long will be a big problem and have an impact on the environment. One solution that can be used for the problem of sawdust waste is to mix this sawdust waste into a concrete mixture. This sawdust waste can be used in concrete mixtures because of the cellulose content in sawdust waste which can affect the compressive strength value with different concrete treatment methods (curing) and slump of concrete. In this research included into experimental research with wood used is wood kamper samarinda, from the leftover cutting of wood frames from craftsman wood UD. kembang Arum in Bekasi, West Java.  Using sawdust waste with a size that passes through sieve No.4 (passes through a 4.75 mm) with variaes addition of 0 kg/m3 , 1 kg/m3  dan 1,5 kg/m3, as well as testing with a concrete mixture that has a mix design of 35 MPa f'c which is inserted into the test object in the form of a cylinder with a diameter and height of 15 and 30 cm which is then for the treatment method done by three different methods. The addition of saw dust waste with a varies of 1 kg/m3  dan 1,5 kg/m3   to the concrete mixture makes the slump and workability values decrease, but the slump value obtained is still in accordance with slump value plan. and for compressive strength values with an addition variation of 1 kg / m3 and 1.5 kg / m3 , The compressive strength value changes from the normal compressive strength value of concrete and the effect of the treatment method also affects the compressive strength value obtained.